Transforming the theory of reading guidance in the information society - T. B. Markova (Библиосфера, 2015)
The article deals with an actual recent problem, which is reading guidance. It considers approaches to the concept of «reading guidance» at all stages of national library science. Their analysis has shown that the following theoretical transformations of reading guidance problem can be traced: 1) transition from a reader individual approach to organizing systematic books reading; 2) forming an ideological orientation and a clear state policy to resolve mass reading; 3) understanding reading guidance as a pedagogical process that plays an important role in young generation upbringing and education. It is proved that reading guidance was the core of individual work with readers in Soviet libraries, and nowadays is a part of the state policy in the field of culture. Trends in terminology changes reflecting the essence of reading guidance are revealed.